Study of maternal and fetal outcome in twin pregnancy - Singh, Lata; Trivedi, Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Multiple pregnancies are associated with an increased risk of obstetric complications as well as perinatal morbidity and mortality especially in developing countries. The present study aims to understand the maternal and perinatal outcomes of multiple and singleton pregnancies delivering at Rajendra Institute of Medical Sciences, Ranchi, India. Aim of study was to investigate the maternal and fetal outcome in twin pregnancies in Rajendra Institute of Medical Sciences (RIMS), Ranchi Methods: This comparative prospective study was conducted in the department of obstetrics and gynecology, Rajendra Institute of Medical Sciences, Ranchi from the period of 1st April 2015 to 30th September 2016. Consecutive sampling was done till the sample size of 75 was reached for both twin and singleton pregnancies. It included all women admitted in antenatal ward and labor room with clinical or ultrasound diagnosis of twin pregnancy after 28 weeks of gestation. Results: The incidence of twins in this study was 1.85%. Mean maternal age was 25.25±4.5 years for twin pregnancies and 23.53 ± 3.3 for singleton pregnancies. Twins were seen more in multigravida (70.7%) as compared to primigravida (29.3%). Preterm labor (74.7%), anemia (44%) and hypertensive disorders (32%) and PPH (13.33%) were the most common complication in twin pregnancies. Significantly higher rate of LSCS were seen in twin pregnancies (32.67%) as compared to singletons 18.67%. Mean weight of first twin was 2.03±0.52kg and for second twin it was 1.98±0.51kg. There was higher incidence of moderate to severe asphyxia, IUGR and higher rate of NICU admissions in twins as compared to singletons. Perinatal mortality rate of monchrionic pregnancy was 30% and it was 10.2% for dichorionic pregnancy which shows a significant association of perinatal mortality rate and chorionicity. Conclusions: Good antenatal care, with increased rest and nutritional supplementation, early detection of fetal and maternal complications together with thorough intranatal and postnatal vigilance, can lower both maternal and fetal dangers.